Wing Loading And Aspect Ratio Of Roundleaf Bats (Family:Hiposideridae) - Azuan, Roslan (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Study on the wing loading and aspect ratio for roundleaf bats of Family Hipposideridae was conducted to describe the habitat use and their flight behaviour based on the analysis of wing loading and aspect ratio gathered. By examining their wing loading and aspect ratio, the habitat segregation and their flight behaviour can be classified according to low, medium and high. The study revealed that the roundleaf bat had relatively high wing loading and low aspect ratio. There were also overlapping in wing loading and aspect ratio within the roundleaf bats. This showed that there are more than one species of roundleaf bats occupied the same habitat. The species that occupied the same habitat may face competition or may adopted resource partition to avoid competition. Species that have low wing loading and aspect ratio have high manoeuvrability and can fly in cluttered habitat whereas species that have high wing loading and aspect ratio have low manoeuvrability and fly in open environment and they can fly in long distance. Wing loading and aspect ratio were used to explain the flight behaviour, flight performance, and habitat preferential.